2011
DOI: 10.1088/2041-8205/728/1/l10
|View full text |Cite
|
Sign up to set email alerts
|

THE MURMUR OF THE HIDDEN MONSTER: CHANDRA 'S DECADAL VIEW OF THE SUPERMASSIVE BLACK HOLE IN M31

Abstract: The Andromeda galaxy (M31) hosts a central supermassive black hole (SMBH), known as M31 * , which is remarkable for its mass (∼10 8 M ) and extreme radiative quiescence. Over the past decade, the Chandra X-Ray Observatory has pointed to the center of M31 ∼100 times and accumulated a total exposure of ∼900 ks. Based on these observations, we present an X-ray study of a highly variable source that we associate with M31 * based on positional coincidence. We find that M31 * remained in a quiescent state from late … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
0
38
1
Order By: Relevance
“…Again, the Galactic clouds of Nishimura et al (2015) lie on the right hand side of this figure and are difficult to compare with M31 measurements. Our measurements are not compatible with Seyfert galaxies, which makes sense because there is no sign of active galactic nuclei (AGN) in M31 (Li et al 2011). Interestingly, on the one hand, the HCN/HCO+ line ratio detected here is compatible with the value (1.5) measured by Liu et al (2013) in infrared dark clouds.…”
Section: Observed Line Ratioscontrasting
confidence: 82%
See 1 more Smart Citation
“…Again, the Galactic clouds of Nishimura et al (2015) lie on the right hand side of this figure and are difficult to compare with M31 measurements. Our measurements are not compatible with Seyfert galaxies, which makes sense because there is no sign of active galactic nuclei (AGN) in M31 (Li et al 2011). Interestingly, on the one hand, the HCN/HCO+ line ratio detected here is compatible with the value (1.5) measured by Liu et al (2013) in infrared dark clouds.…”
Section: Observed Line Ratioscontrasting
confidence: 82%
“…There is a significant continuum flux at 3.6 cm and 6.2 cm, and a weak polarised component (∼10%). There is a relatively flat spectral index (ν β = −0.4 ), while the contribution from the black hole is very weak and localised (Li et al 2011). This flat spectral index cannot be accounted for by an inverted synchrotron emission due to a present AGN, but we cannot exclude relic emission from past AGN activity (e.g.…”
Section: Gas Componentsmentioning
confidence: 99%
“…This circum-nuclear environment is discussed as a region of very high star density around a central black hole in Bender et al (2005) and Li et al (2009). Li et al (2011) recently discussed No. 164 as the X-ray source of the central super-massive black hole (M 31*) and provided a detailed Chandra light curve with an outburst in X-rays.…”
Section: Corementioning
confidence: 99%
“…Therefore, we employed a two-dimensional image fitting method (Li et al 2011) to simultaneously determine the observed fluxes of X1 and X3, which not only maximizes the counting statistics, but also accounts for the propagation of the dominating error arising from the mutual point-spread function (PSF) scattering. Briefly, we fitted the 0.5-8 keV image of the central 60 60 ´ field with a three-component model convolved with the PSF.…”
Section: Revisiting the X-ray Nucleusmentioning
confidence: 99%